Sex-specific responses of Taxus mairei to UV-B radiation involved altering the interactions between the microbiota assembly and host secondary metabolism - Zhang, Hongshan; Hou, Kailin; Liang, Xueshuang; Lin, Wanting; Ma, Ruoyun; Zang, Yue; Zhan, Xiaori; Wang, Mingshuang; Feng, Shangguo; Ying, Qicai; Zheng, Bingsong; Wang, Huizhong; et al. (Microbiome, 2024)
To adapt to constantly changing environments, ancient gymnosperms have coevolved with diverse endophytic fungi that are essential for the fitness and adaptability of the plant host. However, the effect of sex on plant-endophyte interactions in response to environmental stressors remains unknown. RNA-seq integrated with ITS analysis was applied to reveal the potential mechanisms underlying the sex-specific responses of Taxus mairei to ultraviolet (UV)-B radiation. Enrichment analysis suggested that sex influenced the expression of several genes related to the oxidation-reduction system, which might play potential roles in sex-mediated responses to UV-B radiations. ITS-seq analysis clarified the effects of UV-B radiation and sex on the composition of endophytic fungal communities. Sex influenced various secondary metabolic pathways, thereby providing chemicals for T. mairei host to produce attractants and/or inhibitors to filter microbial taxa. Analysis of fungal biomarkers suggested that UV-B radiation reduced the effect of sex on fungal communities. Moreover, Guignardia isolate #1 was purified to investigate the role of endophytic fungi in sex-mediated responses to UV-B radiation. Inoculation with spores produced by isolate #1 significantly altered various oxidation-reduction systems of the host by regulating the expression of APX2, GST7 NCED1, ZE1, CS1, and CM1. These results revealed the roles of endophytic fungi in sex-mediated responses to UV-B radiation and provided novel insights into the sex-specific responses of Taxus trees to environmental stressors. Video Abstract.